Nanoporous Gold Catalyst for the Oxidative N‐Dealkylation of Drug Molecules: A Method for Synthesis of N‐Dealkylated Metabolites. (5th April 2022) - Alipour Najmi, Ali; Jafariyeh‐Yazdi, Elchin; Hadian, Mojgan; Hermans, Jos; Bischoff, Rainer; Yue, Jun; Dömling, Alexander; Wittstock, Arne; Permentier, Hjalmar P.
Abstract: A novel method for the selective catalytic N‐dealkylation of drug molecules on a nanoporous gold (NPG) catalyst producing valuable N‐dealkylated metabolites and intermediates is described. Drug metabolites are important chemical entities at every stage of drug discovery and development, from exploratory discovery to clinical development, providing the safety profiles and the ADME (adsorption, distribution, metabolism, and elimination) of new drug candidates. Synthesis was carried out in aqueous solution at 80 °C using air (oxygen source) as oxidant, in single step with good isolated yields. Different examples examined in this study showed that aerobic catalytic N‐dealkylation of drug molecules on NPG has a broad scope supporting N‐deethylation, N‐deisopropylation and N‐demethylation, converting either 3° amines to 2° amines, or 2° amines to 1° amines. Abstract : Facilitating drug discovery : We describe a novel method for the selective catalytic N‐dealkylation of drug molecules on a nanoporous gold (NPG) catalyst producing valuable N‐dealkylated metabolites and intermediates. Various examples examined in this study showed that aerobic catalytic N‐dealkylation of drug molecules on NPG has a broad scope, supporting N‐deethylation, N‐deisopropylation and N‐demethylation, converting either 3° amines to 2° amines, or 2° amines to 1° amines.